The Literature Review : The Effectiveness of Assertive Attitudes in Reducing Bullying Behavior - Yofita, Yola; Fitriani, Wahidah (Program Studi Bimbingan dan Konseling, 2024)
This research presents a literature review regarding the effectiveness of assertive attitudes in reducing bullying behavior. By collecting and analyzing several articles related to the discussion, this article explores how assertive attitudes can help students face and overcome bullying behavior that is currently widespread. An assertive attitude, which is the ability to express opinions and desires transparently and respect the rights of other people, can really establish good communication with other people, grow self-confidence and create positive social relationships. The results of the analysis show that students who have an assertive attitude are able to reduce the negative impact of bullying behavior. This research can be used as a basis for designing the importance of holding training to increase assertive attitudes as a strategy for creating a safe and comfortable school environment. Thus, strengthening assertive attitudes is expected to be an effective step in reducing bullying behavior in various circles